Pengaruh Green Accounting Dan CSR Disclosure Terhadap Nilai Perusahaan - Julianah; Paniran; Sri Intan Purnama (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the influence of Green Accounting and CSR Disclosure on company value with profitability as a mediating variable. The approach used is causal associative quantitative with secondary data obtained from the company's financial statements and sustainability reports. The sampling technique used purposive sampling so that 60 observations from 12 food and beverage companies were obtained. Data analysis was carried out using panel data regression with the help of the EViews application. The results of the study show that Green Accounting has no effect on the company's value. CSR Disclosure has also not had an effect on the company's value, which shows that social responsibility disclosure is not yet a top consideration for investors. In addition, profitability has not been able to affect the value of the company. In the mediation variable test, Green Accounting has no effect on profitability, while CSR Disclosure has an effect on the company's profitability. However, profitability has not been able to mediate the influence of Green Accounting and CSR Disclosure on company value. Thus, only CSR Disclosure has an effect on profitability, while other variable relationships do not show significant influence